2014
DOI: 10.1093/scan/nsu020
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress modulates oxytocin effects on limbic system during acute psychosocial stress

Abstract: Early life stress (ELS) is associated with altered stress responsivity, structural and functional brain changes and an increased risk for the development of psychopathological conditions in later life. Due to its behavioral and physiological effects, the neuropeptide oxytocin (OXT) is a useful tool to investigate stress responsivity, even though the neurobiological underpinnings of its effects are still unknown. Here we investigate the effects of OXT on cortisol stress response and neural activity during psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 80 publications
5
80
2
Order By: Relevance
“…Recent studies on fear and salience arousal show that OXT reduces amygdala activation and alters amygdala-centered FC to brain regions involved in autonomic-neuroendocrine control (Riem et al, 2012). In our recent study, contrary to the stress-attenuating effect in control subjects, OXT enhanced cortisol stress responses and stress-induced deactivation in limbic areas in subjects who experienced ELS (Grimm et al, 2014). It remains unclear whether stress-induced changes in amygdala-centered FC are also modulated by the joint effect of OXT and ELS.…”
Section: Introductioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Recent studies on fear and salience arousal show that OXT reduces amygdala activation and alters amygdala-centered FC to brain regions involved in autonomic-neuroendocrine control (Riem et al, 2012). In our recent study, contrary to the stress-attenuating effect in control subjects, OXT enhanced cortisol stress responses and stress-induced deactivation in limbic areas in subjects who experienced ELS (Grimm et al, 2014). It remains unclear whether stress-induced changes in amygdala-centered FC are also modulated by the joint effect of OXT and ELS.…”
Section: Introductioncontrasting
confidence: 53%
“…Our second aim was to explore the interaction between ELS and OXT on stress-induced amygdala FC shift. Grimm et al (2014) found that the hippocampus is involved in the interaction effects of ELS and OXT on stress reactivity. We therefore hypothesize a joint effect of EA and OXT on stress-induced FC changes between amygdala and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a mouse model of ASD, chronic intranasal OT administration did not lead to improvements in social behaviors (Bales et al, 2014). Lastly, exposure to ELS seems to alleviate or even reverse the presumed beneficial effects of intranasal OT treatment in humans (Bakermans-Kranenburg and Van Ijzendoorn, 2013; Grimm et al, 2014). Thus, premature use of intranasal OT as a long-term stand-alone treatment or as adjunctive pharmacotherapy in combination with psychotherapy in women with PPD and parenting difficulties that both may be a result of maternal ELS-exposure is potentially harmful to both mother and offspring.…”
Section: Methodsological Challenges Future Directions and Translatmentioning
confidence: 99%
“…In healthy men with a history of ELS, OT has a diminished capacity to downregulate cortisol under basal conditions (Meinlschmidt and Heim, 2007). The stress-dampening effects of intranasal OT on amygdala reactivity may even be reversed in individuals with ELS-exposure; thus, intranasal OT increased cortisol reactivity and hippocampal deactivation after exposure to acute psychosocial stress only in individuals with ELS-exposure (Grimm et al, 2014). This seemingly paradoxical finding may be explained by the social salience hypothesis (Shamay-Tsoory and Abu-Akel, 2015), which postulates that OT increases the salience of social stimuli.…”
Section: Ot and Early-life Stress (Els) – Role In Shaping Neural Cmentioning
confidence: 99%